Observasi Metode Pembelajaran PPKn Di SMP Negeri 35 Medan - Dewi Romantika Tinambunan; Esra Natasya Sitepu; Ivana Theo Philia; Jekson Saragih; Laras Sati Sintania; Ture Ayu Situmeang (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This research is entitled "Observation of Civics Learning Methods at SMP Negeri 35 Medan". This research was carried out with the aim of finding out how and what methods, strategies and innovations can be used to overcome problems in conducting Civics Learning as well as examining the problems faced by teachers in SMP 35 Medan in conducting PPKn learning. This research is useful as a developer of scientific insight regarding teaching and learning strategies implemented by citizenship education teachers at SMP Negeri 35 Medan Jl. William Iskandar New Memories, District. Percut Sei Tuan, Deli Serdang Regency, North Sumatra.